2020
DOI: 10.1039/c9cp04158c
|View full text |Cite
|
Sign up to set email alerts
|

Lipid vesicle composition influences the incorporation and fluorescence properties of the lipophilic sulphonated carbocyanine dye SP-DiO

Abstract: Lipid membrane composition influences insertion efficiency and photophysical properties of lipophilic membrane-inserting dyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
1
19
1
Order By: Relevance
“…In fact, Lubart et al recently demonstrated, using absorbance, fluorescence emission, and fluorescence lifetime measurements, that the incorporation efficiency of SP-DiO is highly dependent on lipid composition and that addition of cholesterol has a significant impact on the photophysical properties of the dye, making such effects very likely also in native lipid membranes of the type investigated in this work. 50 However, irrespective of the actual reason to the deviation from the expected dependence between emission intensity and size, our results demonstrate that membrane dyes of this type do not necessarily serve as reliable markers for the size of small-scale membrane structures with complex biomolecular composition. This insight has impact in several biological processes membrane curvature has been shown to play a significant role, including curvature-selective protein binding and sorting, 28 the activity of membrane-digesting enzymes, 52 and the action of antiviral peptides, 53 to mention a few examples.…”
Section: ■ Conclusionmentioning
confidence: 68%
See 2 more Smart Citations
“…In fact, Lubart et al recently demonstrated, using absorbance, fluorescence emission, and fluorescence lifetime measurements, that the incorporation efficiency of SP-DiO is highly dependent on lipid composition and that addition of cholesterol has a significant impact on the photophysical properties of the dye, making such effects very likely also in native lipid membranes of the type investigated in this work. 50 However, irrespective of the actual reason to the deviation from the expected dependence between emission intensity and size, our results demonstrate that membrane dyes of this type do not necessarily serve as reliable markers for the size of small-scale membrane structures with complex biomolecular composition. This insight has impact in several biological processes membrane curvature has been shown to play a significant role, including curvature-selective protein binding and sorting, 28 the activity of membrane-digesting enzymes, 52 and the action of antiviral peptides, 53 to mention a few examples.…”
Section: ■ Conclusionmentioning
confidence: 68%
“…al. which suggest that the photophysics of SP-DiO depends strongly on the membrane composition of synthetic lipid vesicles 50. …”
mentioning
confidence: 94%
See 1 more Smart Citation
“…20 The possibility to analyze wide size distributions on the individual nanoparticle level without relying on the particle signal−size relation is a key asset for the analysis of biological nanoparticles, such as EVs, exosomes, and viruses, since their size distribution is typically broad, and the fluorescence signal depends strongly on the highly variable membrane composition. 25,32 The identification of tether subpopulations combined with measurements of both size and diffusivity enabled a direct quantitative comparison with theoretical expressions of the size-dependent mobility. The measurements for POPC and EVs were found not to be welldescribed by the equations obtained using the conventional no-slip boundary condition.…”
Section: F Vmentioning
confidence: 99%
“…[32][33][34] However, there is a main issue for lipophilic organic dyes is their low cell penetrability, which can be excluded from cells due to the absence of cell interface-targeting segments, such as cationic charges, which is detrimental for designing specific fluorescent probes, as it has a tendency to provoke attraction toward negatively charged biomolecules (proteins and biomembranes) by opposite charge attractions. [35][36][37] Therefore, the imbalance between hydrophobicity and cell penetrability should be considered in the context of probe designing.…”
Section: Introductionmentioning
confidence: 99%